The paracaspase MALT1 mediates CARD14‐induced signaling in keratinocytes. (25th April 2016) - Afonina, Inna S; Van Nuffel, Elien; Baudelet, Griet; Driege, Yasmine; Kreike, Marja; Staal, Jens; Beyaert, Rudi
Abstract: Mutations in CARD14 have recently been linked to psoriasis susceptibility. CARD14 is an epidermal regulator of NF‐κB activation. However, the ability of CARD14 to activate other signaling pathways as well as the biochemical mechanisms that mediate and regulate its function remain to be determined. Here, we report that in addition to NF‐κB signaling, CARD14 activates p38 and JNK MAP kinase pathways, all of which are dependent on the paracaspase MALT1. Mechanistically, we demonstrate that CARD14 physically interacts with paracaspase MALT1 and activates MALT1 proteolytic activity and inflammatory gene expression, which are enhanced by psoriasis‐associated CARD14 mutations. Moreover, we show that MALT1 deficiency or pharmacological inhibition of MALT1 catalytic activity inhibits pathogenic mutant CARD14‐induced cytokine and chemokine expression in human primary keratinocytes. Collectively, our findings demonstrate a novel role for MALT1 in CARD14‐induced signaling and indicate MALT1 as a valuable therapeutic target in psoriasis. Synopsis: This study shows that the paracaspase MALT1 is indispensable for CARD14‐induced NF‐κB and MAP kinase signaling. Pharmacological inhibition of MALT1 prevents pro‐inflammatory gene expression in primary keratinocytes induced by psoriasis‐associated mutation of CARD14. CARD14 is part of a novel CARD14/BCL10/MALT1 (CBM) signaling complex. MALT1 is indispensable for CARD14‐induced activation of NF‐κB and p38/JNK MAP kinases. Psoriasis‐associated CARD14 mutation enhances MALT1 proteolytic activity towards A20 and CYLD. Pharmacological inhibition of MALT1 prevents mutant CARD14‐induced cytokine and chemokine expression in keratinocytes. Abstract : This study shows that the paracaspase MALT1 is indispensable for CARD14‐induced NF‐κB and MAP kinase signaling. Pharmacological inhibition of MALT1 prevents pro‐inflammatory gene expression in primary keratinocytes induced by psoriasis‐associated mutation of CARD14.